Masayang matuto mula sa Manobo the utilization of an interactive storybook about the importance and significance of the Agusan Manobo's culture and tradition to children, ages 8-10 - Ilano, Peter John O.; Reyes, Mitzi Marie Aguilar (Quezon City College of Fine Arts, University of the Philippines Diliman, 2017)
The Philippines is known to be rich in culture because of the diversity in the traditions, customs and beliefs of the different Philippine ethnolinguistic groups that set the foundation of Filipinos. These groups are important in the preservation of the Philippine culture for they hold histories and accountabilities in the image building of the country. One of them are the Manobo, one of the largest Philippine ethnolinguistic group.

It is the responsibility of the Filipinos to acknowledge, appreciate, learn, and preserve what they have; and that starts with educating Filipinos at their young age. In the curriculum of Araling Panlipunan (AP) given by the Department od Education (DepEd), the topic about the Philippine ethnolinguistic groups are discussed in elementary, fourth grade. The objective of this is to make the students instill the value of unity despite having diverse culture and traditions, and at the end of the course, it is expected of them to be appreciative of the differences of Filipinos. In the research of the visual communicator, the topic about Manobo is not comprehensive nor given much focus to the students. It is because of the lack of research, studies, and also teaching materials about them. With that, the visual communicator proposed to utilize an interactive storybook about the importance and significance of the culture and traditions of Manobo, using paper engineering to children, ages 8-10. This is to reintroduce and help them understand more of Manobo community. The book is equipped with paper engineering to make it more interesting than the usual teaching materials. The book will not only be for children, but it can also be used as a supplementary tool for teaching.
Thesis (Bachelor of Fine Arts in Visual Communication)--University of the Philippines Diliman
Includes bibliographical references
Keywords: Manobos (Philippine people); Ethnolinguistic group -- Philippines; Lumad (Philippine people); Paper engineering